Serum peptide profiling for potential biomarkers in early diagnosis of Escherichia coli bloodstream infection. (August 2019) - Ma, Yating; Chen, Chen; Yang, Ming; He, Shang; Zhang, Kexin; Wang, Chengbin
Highlights: MALDI-TOF MS system was the first time used in the study of serum peptide after E. coli BSI. Using the KNN model to aid in the diagnosis of bacterial BSI. TRF, SAA1 and C3 would be the new cytokines for the diagnosis of BSI. Abstract: Background: Bacterial bloodstream infection (BSI) remains an important cause of morbidity and mortality, which is a widespread and uncontrolled inflammatory response. There are some cytokines for the auxiliary diagnosis, such as procalcitonin (PCT), C reactive protein (CRP), and interleukin 6 (IL-6), which are not sufficient. This study was aimed to explore a new method of diagnosing bacterial BSI and to find some new biomarkers that could differentiate bloodstream infected patients from healthy people. Methods: An animal model was used to find relevant changes of peptides in the serum and was validated in clinical samples. Mice (25–27 g) were randomized to infection with Escherichia coli ATCC25922 or phosphate buffer saline. The serum samples were purified by weak cation exchange beads and the serum peptide profiling was established by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). Statistical analysis and diagnostic modeling were conducted on BioExplorer. Amino acid sequences of the candidate peptides were identified by nano-liquid chromatography electrospray ionization–tandem mass spectrometry and relevant proteins were recognized on the Uniprot database. The identified proteins were confirmed via enzyme-linked immunosorbent assay on clinical samples. Results: Five peptide peaks ( m / z 1941, 2924.1, 3962.1, 4126.9 and 5514) were found as candidate biomarkers for E. coli infection, and the diagnostic model discriminated E. coli infected patients from healthy controls with an accuracy of 92.2%. Peptide peaks m / z 1941, 2924.1 and 4126.9 were identified as the fragments of Serotransferrin (TRF), Complement C3 and Serum amyloid A-1 protein (SAA1), respectively, but only C3 and SAA1 showed significant difference in clinical samples. Conclusion: MALDI-TOF MS could be a new method to find the changes of serum peptides after infection, C3 and SAA1 could be new biomarkers in diagnosing BSI.